ANALISIS KESULITAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPA KELAS V DI SD N 37/II PASAR LUBUK LANDAI KECEMATAN TANAH SEPENGGAL KABUPATEN BUNGO - zi, fauziah; Irawan, Intan Winda; Yanti, Yuli; Guswita, Reni (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2022)
The problems found in the class of SD N 37/II Pasar Lubuk Landai there are 4 students who have learning difficulties, namely Ragil Saputra, Altha Putri Hayu, Rizal Pramono, Nuesupina by showing thesymptoms experrienced by students such as the result obtained are not inaccordance with the efforts made done, slow in doing the task, showing indifference, difficultto focus, showing unnatural behavior such as always noisy, disorganized during learning. So this study aims to determine the form of learning difficulties, and efforts to evercome learning difficulties in class V at SD N 37/II Pasar Lubuk Landai, Tanah Sepenggal Kabupaten Bungo district. This research uses descriptive qualitative research method. Research informants there are 4 students from 9 subjects of class V students who have learning difficulties the data collection techniques used are observation, interviews, and documentations. The research instruments used are observation, sheets, interview guidelines and documentation. Data analysis techniques used are data reduction, data presentation and conclusion drawing. The result of the study indicate that thereare two forms of learning difficulties for students. First, there are 2 students who have learning disabilities, namely learning disabilities,and 2 students who experience slow learning. Factors causing learning difficulties include internal factors in the form of learning motivation. Study habits, attitudes in learning as well as external factors including the famuly, community, and school environment white efforts to overcome leaerning difficulties are to provideasistance in the form of 1) group study guidance 2) individual study guidance 3) remedial teaching 4) personal guidance 5) case transfer.